White Maize to Pigarro: An Actor-Network Analysis of an Improved Crop Variety in Northwest Portugal. Issue Volume 36:Issues 1(2016) (March 2016) - Powell, Joseph B.
Plant breeding is often referred to as a process of crop improvement, and the crop varieties produced by breeders are called improved varieties. Improved crop varieties bear trademarked names and they fill food systems and farming landscapes across the world, thus comprising a large portion of terrestrial biodiversity taken up in agriculture. Outside a narrow field of literature dealing with plant breeding and agricultural science, very little is known about what exactly constitutes an improved crop variety, and how these improvements impact existing and future relationships between people and crops. In essence, what is an improved crop variety? In this paper, I explore how a particular type of white maize in northwest Portugal is transformed into an improved variety named Pigarro through an experimental type of participatory plant breeding (PPB). I draw upon ethnographic fieldwork conducted on the project using an Actor-Network Theory (ANT) conceptual framing to suggest that this transformation constitutes an ontological shift beyond the conceptual-taxonomic level. Rather, the key difference between white maize and Pigarro has to do with the wide range of human and nonhuman actors who are enrolled in the project. ANT provides a lens into the constant work of social world ordering that takes place around producing and reproducing Pigarro . Thus, I argue for a relational ontology that understands crop varieties as actor-networks and collectives of humans and nonhumans, rather than as forms of socially purified biophysical nature.